1981
DOI: 10.2134/agronj1981.00021962007300040004x
|View full text |Cite
|
Sign up to set email alerts
|

Protein, Oil, and Energy Yields of Sunflower as Affected by N and P Fertilization1

Abstract: Relatively little information exists on the N and P needs of sunflower (Helianthus annuus L.) on infertile soils in non‐traditional production areas. The effects of four levels each of N (0 to 180 kg/ha) and P (0 to 60 kg/ha) applied to a thermic Typic Rhodustult were evaluated over three seasons. In all seasons there were highly significant seed yield responses to N and P a plied. The nature of the N ✕ P interactions indicated a greater response to N fertilization where P had been applied than in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 3 publications
7
16
0
1
Order By: Relevance
“…It is noteworthy that compared to the control the highest N rate produces in a 9% increase in protein concentration. Previous research has indicated that nitrogen fertilization tends to increase seed protein content at the expense of oil (Blamey andChapman 1981, Steer et al 1986). …”
Section: Seed Protein Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that compared to the control the highest N rate produces in a 9% increase in protein concentration. Previous research has indicated that nitrogen fertilization tends to increase seed protein content at the expense of oil (Blamey andChapman 1981, Steer et al 1986). …”
Section: Seed Protein Concentrationmentioning
confidence: 99%
“…Numerous studies have investigated the effects of N fertilization on sunflower in the various parts of the world (Hussein et al 1980, Blamey and Chapman 1981, Kandil 1984, Narwal and Malik 1985, Khokani et al 1993, Legha and Giri 1999, Tomar et al 1999, Zubillaga et al 2002. Nitrogen is commonly a limiting factor in sunflower production (Zubriski andZimmerman 1974, Robinson 1978).…”
mentioning
confidence: 99%
“…Kamel et al (1980) reported that nitrogen application did not affect the oil content of sunflower seed either way. On the other hand, Blamey and Chapman (1981) and Kasem and El-Mesilby (1992) observed that increased doses of N application decreased the oil contents of sunflower seed. Similar results were also reported by Nazir et al (1986), but Steer et al (1986) and Manoharan et al (1991) reported that oil contents of sunflower seed were increased by N fertilizer.…”
Section: Introductionmentioning
confidence: 97%
“…One reason for this behavior is the high-energy requirements of the oil, the final sink of photoassimilates (Andrade, 1995). Another problem related to this crop is that its large nitrogen (N) uptake reduces oil production (Blamey and Chapman, 1981). Knowledge about the effects of nutrient supply on sunflower and fertilization technology has increased significantly in the last few years (Loubser and Human, 1993;Zubillaga et al, 2002).…”
Section: Introductionmentioning
confidence: 99%